MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR SISWA - Muhammad Saefudin, Chodidjah Makarim (LP2M Universitas Muslim Nusantara Al Washliyah, 2020)
This study aims to determine the great level of motivation possessed by students in studying SKI at MTsN Bogor City, knowing the learning achievements obtained by students in studying SKI at MTsN Bogor City and to determine whether there is a relationship between student motivation and student learning achievement at Class VIII SKI subjects in Bogor City Madrasah Tsanawiyah Negeri. The research method used was a survey research method with data collection techniques in the form of questionnaires or questionnaires and the documentation and research objects totaling 50 students. The results of this study indicate that the significance value of the above output is 0.843, which means more than 0.05, therefore the conclusion of the significance test above is that Ho is accepted and Ha is rejected, meaning that there is no relationship between learning motivation with students' learning achievement at SKI subjects in Bogor City MTsN. So the better the motivation to learn that is obtained by students, the more academic achievement each student has.